2022
DOI: 10.1155/2022/3584192
|View full text |Cite
|
Sign up to set email alerts
|

miR-486-5p Restrains Extracellular Matrix Production and Oxidative Damage in Human Trabecular Meshwork Cells by Targeting TGF-β/SMAD2 Pathway

Abstract: Background. Glaucoma is characterized by elevated intraocular pressure caused by aqueous outflow dysfunction. Trabecular meshwork plays a key role in controlling intraocular pressure by modulating aqueous outflow. This study investigated the protective effects of miR-486-5p in H2O2-stimulated human trabecular meshwork cells (TMCs). Methods. TMCs were disposed with 300 μM H2O2 to establish oxidative damage models in vitro. miR-486-5p mimics and its controls were transfected into TMCs, and cell apoptosis and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Several important signaling regulators, such as PTEN, FOXO1, and SIRT1, have been identi ed as targets of miR-486-5p [14]. Extensive studies have revealed that miR-486-5p is involved in the regulation of resistance to oxidative damage and the inhibition of collagen hyperproliferation, and brosis [44][45][46]. Downregulated expression of miR-486-5p has been observed in the serum and lung tissues of patients with silicosis and idiopathic pulmonary brosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several important signaling regulators, such as PTEN, FOXO1, and SIRT1, have been identi ed as targets of miR-486-5p [14]. Extensive studies have revealed that miR-486-5p is involved in the regulation of resistance to oxidative damage and the inhibition of collagen hyperproliferation, and brosis [44][45][46]. Downregulated expression of miR-486-5p has been observed in the serum and lung tissues of patients with silicosis and idiopathic pulmonary brosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-486–5p is a plasma and extracellular vesicle-enriched miRNA ( Douvris et al, 2022 ). As shown by the results of small RNA sequencing, miR-486–5p was downregulated in POAG patients ( Hubens et al, 2021 ), and transfection of miR-486–5p mimics in TM cells can significantly inhibit H 2 O 2 -stimulated ECM remodeling by blocking the TGF-β2/Smad2 signaling pathway ( Xu et al, 2022 ). MiR-483 generally exists in two mature forms, miR-483–3p and miR-483–5p, in the body and is closely related to cell proliferation and tumor development ( Watson et al, 2013 ; Zhou et al, 2018 ).…”
Section: Gene Therapymentioning
confidence: 99%
“… miR-29 human TM cell ( Luna et al, 2009 ; Villarreal et al, 2011 ) Suppressing various EMC, like SPARC, collagen I, collagen IV, and laminin expression and negatively regulate genes involved in ECM deposition and remodeling. miR-486–5p human TM cell ( Xu et al, 2022 ) Inhibiting H 2 O 2 -stimulated ECM remodeling by blocking TGF-β2/Smad2 signaling pathway. miR-483–3p human TM cell ( Shen et al, 2015 ) Protecting TM cell from 300 μM H 2 O 2 induced-fibrosis by inhibiting TGF-β2/Smad4 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, miR-200c is a valuable candidate for future therapeutic approaches in glaucoma research by regulating TM cell contraction. In addition, miR-486-5p can reduce the production of ECM and oxidative damage in human TM cells by targeting the TGF-β/SMAD2 pathway [101]. Overall, future miRNA-based therapies that focus on controlling the production of ECM, regulating TM cell contraction, or targeting the TGF-β may provide novel therapeutic approaches for glaucoma.…”
Section: Micrornas In Trabecular Meshwork (Tm)mentioning
confidence: 99%